Pemahaman Guru PAUD Tentang Pembelajaran Berbasis STEAM dengan Penggunaan Media Loose Parts di Desa Bukit Harapan - Nurul Qomariyah; Zahratul Qalbi (JECED : Journal of Early Childhood Education and Development, 2021)
This study aims to describe the level of understanding of PAUD teachers or PAUD educators about loose parts games. The research method used is qualitative, using the method of direct interviews with early childhood teachers in Bukit Harapan Village, Pinang Raya District, North Bengkulu Regency. The sample used is 3 teachers who teach in one of the PAUD schools. From the results of the interview, it was found that the teacher did not understand the loose parts game. And schools have not applied STEAM-based learning by using learning media in the form of loose parts. So that to overcome the lagging behind modern learning, the teachers at these schools will try to find information about STEAM-based learning so that they can keep up with the times and children's creativity can also be maximized.